Islamic Family Law(s) in Finland: Reflections on Freedom of Religion from the Wellbeing Perspective - Al-Sharmani, Mulki (Temenos, 2022)
A central premise of the concept of freedom of religion is that the state has the obligation and authority to regulate and protect the religious rights of individuals and religious communities. However, this entails the state’s navigation of the rights of citizens vis-à-vis the norms of their religious communities, which in some cases may be in tension. The state must also maintain the country’s central legal principles. These premises are interconnected in vexing ways. This article studies how the concept of freedom of religion, with these underlying premises, applies to the practice of Islamic law in Finland. This question is reflected through an analysis of Finnish Muslims' marriage practices. We argue for a nuanced understanding of the relationship between Islamic family law and freedom of religion. Towards this goal we employ the concept of wellbeing (building on Sarah White 2010) to locate the practice of Islamic family law in Finnish Muslims’ daily lives, whereby they pursue material, relational, and ethical needs and aspirations. We analyse how individuals conclude their marriages and the diverse motivations and meanings underlying these practices. Our aim is to capture the familial, economic, racial, political, and ethical processes through which Finnish Muslims continually and dynamically organize marriage (and divorce) and the implications for their freedom of religion on the one hand and for the Finnish state on the other. Our analysis draws on interview data collected in an ethnographic study of Muslim marriage and divorce practices in Finland in the period between 2013 and 2018.